2014
DOI: 10.1186/1471-2164-15-778
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for behavioral reactivity to social separation and humans in sheep using the OvineSNP50 BeadChip

Abstract: BackgroundCurrent trends in sheep farming practices rely on animals with a greater level of behavioral autonomy than before, a phenotype that actively contributes to the sustainability of animal production. Social reactivity and reactivity to humans are relevant behavioral traits in sheep, known for their strong gregariousness and weak tolerance to handling, which have previously been reported with moderate to high heritabilities. To identify loci underlying such behaviors, we performed a genome study in Roman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 68 publications
1
27
0
Order By: Relevance
“…Further work is needed to validate a practical on-farm assessment of fear of humans that could be applied to extensive systems. Recent studies by Hazard et al [51,52] have investigated several behavioral traits in sheep that could be used to validate the assessment of fear of human in extensive farming conditions. Additionally, limited work has been done to develop practical on-farm assessments for clinical and sub-clinical mastitis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to validate a practical on-farm assessment of fear of humans that could be applied to extensive systems. Recent studies by Hazard et al [51,52] have investigated several behavioral traits in sheep that could be used to validate the assessment of fear of human in extensive farming conditions. Additionally, limited work has been done to develop practical on-farm assessments for clinical and sub-clinical mastitis [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for the GDMR trait, we investigated differences between lamb families by testing a family effect (10 classes), nested in the year effect, according to the GLM procedure describe above. This was only used for GDMR because the genetic variability of the other traits included in the present study has already been described ( Bibé et al, 2002 ; Allain et al, 2014 ; Hazard et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…They found no QTL overlaps on these two traits which supports the hypothesis that different genetic factors influence behavioural responses to different situations (Gutierrez-Gil et al 2008). In sheep, Hazard et al (2014) found no QTL overlaps for the different behaviour traits tested. Hence, the behavioural responses in domestic sheep to social separation and exposure to humans are under polygenic influence.…”
Section: Physiology and Morphologymentioning
confidence: 52%